Impact of Risk Factors for Gestational Diabetes (GDM) on Pregnancy Outcomes in Women with GDM in a Single Center Study in Rural Area - Alam, Md Shah; Nipa, Shamim Ara; Nargis, Hasnahena; Kabir, Mohammad Ahsanul; Ali, Md Haidar (Archives of Clinical and Biomedical Research, 2024)
Background: Gestational diabetes mellitus (GDM) is a kind of hyperglycemia that initially appears or is detected during pregnancy, which is one of the most common obstetric complications. Gestational diabetes mellitus (GDM) is a unique metabolic disorder that occurs during pregnancy. Both GDM and advanced age increase the risk of adverse pregnancy outcomes. Objective: The aim of this study is to evaluate the impact of risk factors for gestational diabetes (gdm) on pregnancy outcomes in women with gdm. Methods: The cross-sectional observational study was conducted in Joypara Clinic and Diabetic Center, Dhaka, Bangladesh from June 2017 to May 2023. A total of 183 women with gestational diabetes were enrolled and analyzed in this study. The questionnaire was pretested, corrected and finalized. Data were collected by face-to-face interview and analyzed by appropriate computer based programmed software Statistical Package for the Social Sciences (SPSS), version 24. Results: In this study, majority 84 (45.9%) of the patients were in 21 – 30 years age group and 63 (34.4%) patients were in >30 years age group, Mean±SD of age was 32.6 ± 5.4 years. Most of the patients 102 (55.7%) were housewife. About 49 (26.8%) patients were completed their higher secondary, 29 (15.8%) were completed graduation and 22 (12.0%) were illiterate and majority of the patients 141 (77.0%) came from rural area. Most of the patients 87 (47.5%) were in ≤ 24.9 kg/m2, 64 (35.0%) of the patients were in the range of 25 – 29.9 kg/m2, and 32 (17.5%) of the patients were overweight (≥30). Nullipara was found in 84 (45.9%) patients and multigravida was found in most of the patients 107 (58.5%). Antenatal care was found regular in 92 (50.3%) patients. Preterm pregnancy was found in majority 112 (61.2%) of the patients. Systolic and diastolic blood pressure were found 123.67 ± 12.73 and 85.00 ± 7.31. Cholesterol, LDL, HDL, triglycerides were found 252.0 ± 52.4, 131.6 ± 43.2, 68.8 ± 15.5, 225.6 ± 99.3. HbA1c % was found 5.3 ± 0.4 (34 ± 6). Insulin therapy was needed in 87 (47.5%) and cesarean section was done in 118 (64.5%) patients. Pre-eclampsia, anemia, postpartum hemorrhage, abnormal fetal position and preterm birth were found in 12 (6.6%), 16 (8.7%), 8 (4.4%), 17 (9.3%) and 21 (11.5%) cases. Average birth weight was found in 56 (30.6%) neonates, LBW was found in 82 (44.8%) neonates and very LBW was found in 45 (24.6%) neonates. hypoglycemia and hyperbilirubinemia were found in 18 (9.8%) and 9 (4.9%) neonates, admission to NICU was needed for 34 (18.6%) neonates, respiratory distress syndrome was found in 25 (13.7%) neonates and neonatal death was occured in 3 (1.6%) cases. Conclusion: In pregnant women with GDM was an independent risk factor for pregnancy outcomes in women. Pregnant women with GDM aged over 40 years was an independent risk factor for SGA. This shows the necessary of paying greater attention to GDM and improving prenatal care to enhance pregnancy outcomes of them.